Selected Areas of Psychological Support for Gifted Students - Andrzej Edward Sękowski; Martyna Maria Płudowska (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: After nearly a century of analysis, gifted students' education has evolved into a complex scientific discipline with its own methods, teaching practices and research programs. Solutions are sought that ensure, gifted children and adolescents the optimal conditions for developing their potential. It requires taking into account knowledge of the psychological mechanisms responsible for the development of abilities, achievements and the well-being of gifted individuals Research Aim: The purpose of the article was to identify psychological areas of support for gifted students. The literature on theoretical findings on the structure of giftedness was reviewed, and the results of research on selected characteristics of people belonging to this special group were analyzed. Evidence-based Facts: Based on the analysis of models of outstanding abilities and available empirical research on the difficulties and problems of gifted people, the importance of psychological support in the emotional-motivational sphere, social sphere, personality sphere, development of creativity and within the family system of gifted people is indicated. Summary: Institutional support of gifted students, adapting curricula to their needs and abilities should go hand in hand with psychological measures for harmonious development and shaping the well-being of these individuals.